The Magnitude of Pain-Driven Sympathetic Activation after Surgery and its Gastrointestinal Consequences: A Community-Based Clinical Study - Usama Mazhar, Hina Sagheer, Imam Alam, Inamullah, Rafi Ullah, Rahil Mahmood ur Rahman (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Postoperative pain is a major physiological stressor that activates the sympathetic nervous system, leading to systemic effects beyond patient discomfort. This study aimed to evaluate the magnitude of pain-driven sympathetic activation after surgery and its impact on gastrointestinal recovery in a community-based clinical setting. Methods: This clinical study was conducted from May 2022 to June 2023 at tertiary care hospitals in Lahore, Pakistan, including Doctors Hospital & Medical Centre and Pakistan Kidney and Liver Institute & Research Centre. A total of 100 adult patients undergoing elective surgical procedures were enrolled using consecutive non-probability sampling. Postoperative pain was assessed using the Visual Analog Scale (VAS), and patients were categorized into mild, moderate, and severe pain groups. Sympathetic activation was evaluated through heart rate, blood pressure, and serum catecholamine levels. Gastrointestinal outcomes included time to first bowel sound, passage of flatus, bowel movement, and incidence of postoperative ileus. Statistical analysis was performed using SPSS version 26, with p ≤ 0.05 considered significant. Results: Patients with higher pain scores demonstrated significantly increased sympathetic activity, reflected by elevated heart rate, blood pressure, and catecholamine levels (p < 0.001). Severe pain was associated with delayed gastrointestinal recovery, including prolonged time to bowel sounds (33 ± 6 hours), first flatus (50 ± 7 hours), and bowel movement (74 ± 9 hours). The incidence of postoperative ileus was also significantly higher in the severe pain group (33.3%) compared to moderate (15.4%) and mild pain groups (7.1%) (p < 0.001). Conclusion: Pain-induced sympathetic activation significantly impairs gastrointestinal recovery after surgery. Effective pain management strategies are essential not only for symptom relief but also for reducing postoperative complications and improving clinical outcomes. Keywords: Postoperative pain, Sympathetic activation, Gastrointestinal motility, Postoperative ileus, Catecholamines, Surgical outcomes, Pakistan.